Academic entrepreneurship in universities of the department of Atlántico - Naranjo, Gloria María; Sánchez Rojas, Damaris (Universidad Francisco de Paula Santander, 2015)
From their third mission, universities assume the commitment to become agents that generate social-economic growth and improve the quality of life in their environment of influence, based on technological development and the subsequent transfer of these research and innovative projects to the business environment and society. This article is an exploratory-descriptive study, directed to a selective sample of researchers, who have developed actions of technological transference linked to Public and Private Universities of the Department of Atlántico, identified the particularities of the profile of the enterprising researcher considering own characteristics, abilities, motivations and risk perception, to evidence these conditions from a personal perspective and the institutional context, highlighting an important base of actions and motivations towards a context of academic entrepreneurship in Universities of the Department and institutional factors that are becoming more and more propitious to favor these processes. Based on the variables described and analyzed in the research, three types of strategies that allow the development of this role are suggested. These are: Encouragement strategies; Promotion and training strategies; and evaluation strategies.